'A good method of quitting smoking' or 'just an alternative to smoking'? Comparative evaluations of e-cigarette and traditional cigarette usage by dual users. Issue 1 (January 2017) - Vandrevala, Tushna; Coyle, Adrian; Walker, Victoria; Cabrera Torres, Joshelyn; Ordoña, Izobel; Rahman, Panna
The development of e-cigarettes was initially hailed as a resource in facilitating a reduction in or cessation of cigarette smoking. Many users of e-cigarettes are 'dual users', smoking traditional cigarettes and e-cigarettes. The present qualitative study examines the factors that a group of 20 dual users considered to have been influential in their decisions to use e-cigarettes and their comparative evaluations of e-cigarettes and traditional cigarettes. Health concerns were not found to be sole motivators. Participants pointed to financial and contextual considerations, particularly peer influence on uptake and continued usage of e-cigarettes. E-cigarettes were evaluated as comparable to cigarettes in some ways but not in other important respects such as sensation and satisfaction. Different social evaluations of cigarette and e-cigarette usage were discerned which influenced how participants identified as smokers, 'vapers' or neither. Findings are discussed in relation to social representations, identity and implications for continued e-cigarette usage among dual users.